Projections of two-particle correlations onto transverse rapidity in Au+Au collisions at √sNN = 200 GeV at STAR - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2022)
Two-particle correlation measurements projected onto two-dimensional, transverse rapidity coordinates (yT1,yT2) provide an independent, orthogonal view of the multidimensional correlation distribution that is most often studied via angular projections. As such, these independent transverse projections allow access to manifestations of dynamical fluctuations in relativistic heavy-ion collisions that angular-correlation measurements may not be sensitive to. We report nonidentified charged-particle correlations for Au+Au minimum-bias collisions at √sNN=200 GeV taken by the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). ...